Aprendizagem Cooperativa fundamentos, pesquisas e experiências educacionais brasileiras - Morais, Alessandra de (Editora Oficina Universitária, 2021)
We highlight the relevance of this work for Brazilian Education, considering the need to implement teaching and learning methodologies such as Cooperative Learning, which focuses on working with knowledge, in an active and interactive way, systematized in small heterogeneous groups and favoring the development of cooperative skills, motivation for learning and moral autonomy of students, in an inclusive perspective. In this sense, this work is of great value for educators and educators, as well as for researchers of the subject, for bringing the main theoretical references on which Cooperative Learning is based, for having its development as a field of knowledge, as well as for presenting empirical research carried out in the Brazilian educational reality.